Two Cheers for Richards and Smith: Beyond Anti‐Politics?. Issue 3 (17th May 2016) - Marsh, David; Vines, Emma; Halupka, Max
Abstract: In a recent issue of The Political Quarterly, Richards and Smith critiqued Flinders' work on anti‐politics, suggesting that there needs to be much more focus on supply‐side explanations and recognising that much of the problem lies with politicians, contra Flinders. Here, we argue instead that it is crucial to recognise how supply‐side and demand side explanations interact. For us, politicians need to be more responsive to citizens, but, at the same time, citizens need to recognise problems of contemporary governing. Overall, much is changing in the way in which citizens engage and it is crucial that these changes are understood.